Professoras experientes que ensinam matemática nos anos iniciais : percursos de formação e ensino - Feitosa, Silmara Lopes da Costa (2021)
This study was developed in the research line of Education in Sciences and Mathematics Education in the Study and Research Group in Mathematics Education (GRUEPEM). This research seeks to answer the investigation problem: how the training paths and the process of teaching and learning mathematics manifest themselves in the narratives of experienced teachers from the early years? Therefore, we introduce as main objective comprehend the training paths and the process of teaching and learning mathematics in professional development trajectory of experienced teachers from the early years of elementary school. To build the theoretical and methodological framework we resort to discussions on the professional constitution of the teacher who teaches Mathematics with the authors Nacarato, Mengali e Passos (2009); Pimenta (2017); Serrazina (2012) e Gatti (2010); about Mathematics in the school context, we referenced the theorists: Moura (2007, 2010); Santos (2014) e Palma (2010). About teacher training and professional development cycle our contribution was in Garcia (1999), Marcelo e Vaillant (2012), Day (2001) Nóvoa (1995 e 2019) e Huberman (1995), Dewey (2010) has guided us throughout the discussions about the experiences. The methodological path wasbased on Clandinin e Connelly (2011). Three teachers from the municipal education network of Várzea Grade (MT) who work in the Cycle of Citizen Alphabetization (CBAC) of Elementary School participated in the research. The sources of data production were the narrative interviews and the researcher’s field notes. The data were organized and analyzed in two thematic axes: the professional career of teachers and the formative movements; constitution of good practices of teaching and learning Mathematics in a school context: possibilities, challenges and knowledge potentiated. On this path we seek the possibility of understanding the subject’s experience through the storytelling of his life, those built individually and socially, as well as identifying the personal paths and trajectories and subject training, highlighting the issues and the learning process from the teachers who experienced teach Mathematics in the early years. In revealing these experiences, we realized that there was no process and/or negative imprints about the discipline in the school formation of our protagonists. It became explicit, in this formative context, the experience of a mathematical education marked by mechanized and repetitive practices, without contextualization of the contents taught, this may have resonated in their first practices as teachers who teach mathematics. The course of pedagogy, the courses of continuing training in mathematics, the practice of classroom and the exchange of experience with other teachers, were the formative spaces and sources revealed in the narratives. The voices highlight the appreciation of mathematics as a dynamic and historical science and emphasized the use of manipulative materials and games in the math class. Emerges as challenges present in the teaching of mathematics, the conceptual gaps of students, the lack of material resources, the objective working conditions and, at the present time, the pandemic context. The research indicates the importance of investment in continuous education and school as a formative space.